CMOS Indoor Light Energy Harvesting System for Wireless Sensing Applications - Ferreira Carvalho, Carlos Manuel; Paulino, Nuno Filipe Silva Veríssimo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book discusses in detail the CMOS implementation of energy harvesting.  The authors describe an integrated, indoor light energy harvesting system, based on a controller circuit that dynamically and automatically adjusts its operation to meet the actual light circumstances of the environment where the system is placed.  The system is intended to power a sensor node, enabling an autonomous wireless sensor network (WSN). Although designed to cope with indoor light levels, the system is also able to work with higher levels, making it an all-round light energy harvesting system.  The discussion includes experimental data obtained from an integrated manufactured prototype, which in conjunction with a photovoltaic (PV) cell, serves as a proof of concept of the desired energy harvesting system.  ·         Discusses several energy sources which can be used to power energy harvesting systems and includes an overview of PV cell technologies  ·         Includes an introduction to voltage step-up circuits, with a special emphasis on switched-capacitors (SC) DC-DC voltage converters, energy storing devices and maximum power point tracking (MPPT) techniques  ·         Presents a complete design flow of an indoor light energy harvesting system designed and implemented in a CMOS technology.
Introduction -- Energy Harvesting Electronic Systems -- Photovoltaic Cell Technologies -- Voltage Step-Up Circuits -- Proposed Energy Harvesting System -- Layout of the System -- Experimental Evaluation of the Prototype -- Conclusions and Future Perspectives.
Keywords: Electronic circuits; Energy harvesting; Electronics; Electronic Circuits and Systems; Energy Harvesting; Electronics and Microelectronics, Instrumentation